The functioning of the vocational and technical education system of Ukraine in the war and post-war periods : from stagnation to development - Melnyk, Sergii [Verfasser] (My University, 2024)
„Article reviews the implications and ramifications of the military aggression and war launched by the Russian Federation against Ukraine for the functioning of the VET system and VET provision in Ukraine. The analysis is started by reviewing institutional changes of the VET system and provision in the period from the establishment of Ukraine as independent country in 1991. Then there are presented and discussed direct implications of the war to the VET provision and functioning of the VET system, by talking into considerations impact of the war to the infrastructure, learners, teaching staff, enrolments, and graduation from the VET schools.“ (Autorenreferat; BIBB-Doku)
Keywords: S System beruflicher Bildung; S 3.1 Berufsbildende Schulen; I 2.2.2 Osteuropa; 370; Berufsbildung; Berufsbildungssystem; Berufsbildendes Schulwesen; Ausbildungsangebot; Ukraine; 1991-2024